Thermal-Hydraulic Performance Analysis and Tube Inlet Orifice Design of a Once-Through Steam Generator. Issue 3 (31st December 2021) - Han, Hun Sik; Kim, Young In; Bae, Youngmin; Kim, Sang Ji
Abstract: A numerical study is conducted for a thermal-hydraulic performance analysis and secondary side screw-type tube inlet orifice design of a once-through steam generator. Various tube-plugging conditions and power levels are considered, and the secondary coolant flow rate is adjusted to maintain a constant level of thermal power. Comprehensive numerical solutions are acquired to evaluate the thermal-hydraulic performance and minimum orifice length of the once-through steam generator under various operating conditions. The results obtained show that constant thermal power can be maintained by properly adjusting the secondary coolant flow rate with variation of the steam outlet superheat degree and secondary coolant pressure drop when the once-through steam generator operates at a high power level. The secondary coolant flow rate curve for constant thermal power operation is determined, and the required minimum orifice length to suppress the flow oscillation below the allowable level is evaluated. The lowest power level results in the highest minimum orifice length, and the non-plugged condition practically limits the orifice length criterion. This orifice length and corresponding pumping power are compared with those when the secondary coolant pressure at the tube outlet is controlled for constant thermal power operation.